2022
DOI: 10.1080/01614940.2022.2079809
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of metallic catalysts for the design of selective processes

Abstract: Fine-tuned interaction between reacting molecules and metal surface is of great importance in heterogeneous catalysis for the design of highly selective processes. Conventional strategies based on adjusting the intrinsic catalyst properties such as particle size, metal-support interaction and morphology suffer from complicated and time-consuming synthetic procedures. Recently, the modification of metal nanoparticles with nonmetallic promoters has been demonstrated as an effective tool to regulate the interfaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 198 publications
0
6
0
Order By: Relevance
“…The catalysts demonstrate a partial decrease of the catalytic activity with pyridine and almost full deactivation with piperidine. However, the selectivity to octanal still decreases with the increase of the conversion of 1-octanol, indicating the absence of a partial poisoning effect …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The catalysts demonstrate a partial decrease of the catalytic activity with pyridine and almost full deactivation with piperidine. However, the selectivity to octanal still decreases with the increase of the conversion of 1-octanol, indicating the absence of a partial poisoning effect …”
Section: Resultsmentioning
confidence: 98%
“…However, the selectivity to octanal still decreases with the increase of the conversion of 1-octanol, indicating the absence of a partial poisoning effect. 38 The key question concerning the application of the TEMPO-Ru-BEA catalyst for the oxidation of 1-octanol to octanal is the stability of the catalyst toward TEMPO leaching or the deactivation of the active sites. The stability of the catalyst was studied for five cycles, with intermediate separation of the catalyst by centrifugation.…”
Section: Effect Of Tempo On the Oxidation Of Alcoholsmentioning
confidence: 99%
“…Recently, modification of the metal catalyst with nonmetallic elements has become an efficient strategy to design highly selective bifunctional catalysts, 12,13 where the nonmetallic promoters exert both steric and electronic functionalities. 14,15 In addition, depending on the synthesis methods, the intimacy of metal and nonmetallic promoters can be tuned, which influences the catalytic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, modification of the metal catalyst with nonmetallic elements has become an efficient strategy to design highly selective bifunctional catalysts, , where the nonmetallic promoters exert both steric and electronic functionalities. , In addition, depending on the synthesis methods, the intimacy of metal and nonmetallic promoters can be tuned, which influences the catalytic behavior. , Among the nonmetal-promoted bifunctional catalysts, amine-, phosphine-, and sulfur-based catalytic systems have been successfully used in the selective hydrogenation of the aldehyde group, hydroperoxide production, etc. In previous studies, we have observed that modification of Pd catalysts by iodine and bromine resulted in bifunctional catalysis during the hydrogenation of furfural and 5-hydroxymethylfurfural (HMF) toward ether and dimethylfuran, respectively. The generation of acidity has been proposed by the heterolytic dissociation of hydrogen over the halogen-metal sites. , Later, iodine-modified Pd nanoparticles were used for hydrogenative ring-opening reactions of C6 furan aldehydes to 2,5-hexanedione .…”
Section: Introductionmentioning
confidence: 99%
“…Colloidal synthesis proved to be a successful strategy to prepare ligand‐covered TMP nanocatalysts with controlled crystallinity and morphology [17–20] . Generally, the influence of native or added ligands on nanocatalysts originates from structural (templating, self‐assembly, orientation) and electronic (Fermi level tuning) effects [21] . However, the effect of ligands, such as phosphines, on catalytic reactions was scarcely investigated for TMP.…”
Section: Introductionmentioning
confidence: 99%